Intraoperative Identification of the Intersegmental Plane: From the Beginning to the Future - Zhang, Xianfei; Li, Chengqiang; Jin, Runsen; Li, Hecheng (Frontiers in Surgery, 2022)
Segmentectomy has played a crucial role in the treatment of early-stage lung cancer after the publication of JCOG0802, which indicated that patients with small-sized peripheral non-small-cell lung cancer could receive better survival from segmentectomy than lobectomy despite a higher local recurrence. The intraoperative identification of the intersegmental plane ensures complete resection of the lesion with sufficient margin so that it is deemed as the critical part of segmentectomy. Diverse methods have been developed to acquire distinguishable and lasting borderline between segments, but none of them is proved perfect. In this review, we searched and classified these techniques that emerged from the beginning when segmentectomy was used for bronchiectasis until now. Comparisons between different ways in mechanisms, facility, and safety were made to depict a comprehensive landscape for surgeons to select fit one. Furthermore, we presented our vision for the future of intersegmental plane identification.